ANALISIS KETERCAPAIAN KOMPETENSI DASAR PESERTA DIDIK MELALUI PEMBELAJARAN PREDICT, OBSERVE, EXPLAIN (Universitas Negeri Semarang, 2019)
The purpose of this research is to determine the achievement of students' knowledge competence on the salt hydrolysis subject matter through learning POE models. The research method used is a qualitative descriptive method. The qualitative descriptive method is a research conducted to explain systematically factual and accurate about the facts and nature of a particular population. The research procedure starts by designing instructional tools, performing expert validation, instrument testing, giving POE learning treatment and doing posttest. Subjects in this research were students of class XI IPA 1 and XI IPA 3 SMA Negeri 1 Demak taken on the advice of the teacher or purposive sampling technique. The research design used is a quasi-experimental design. Collecting data using the methods of testing, and documentation. The results showed that students obtain a percentage of classical completeness in class XI IPA 1 and XI IPA 3 which reached 76,32% and 78,95%. Students who complete knowledge competence in class XI IPA 1 as many as 29 students and class XI IPA 3 as many as 30 students. Based on the results of the research can be concluded that with the model POE, students are able to achieve knowledge competence.